Effect of Mercerization and Acetylation on Properties of Coconut Fiber and its Influence on Modified Bitumen - Tan, I.A.W; Wu, W.H; Chan, R.A; Lim, L.L.P (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Coconut fiber, one of many types of natural fibers, is an agricultural waste which is left unutilized after the coconut fruits and juice are extracted. In this research, the effect of the different chemical treatments on the morphological, chemical and physical properties of coconut fiber and its influence on the properties of the modified bitumen were studied. The mercerization effectively altered the surface morphology and reduced the diameter of the coconut fiber. The waxy layer present on the surface of the coconut fiber was significantly reduced after mercerization. Acetylation reported minor reduction on the waxy layer and did not cause any significant changes on the diameter of the coconut fiber. The chemical characterization reported that the hemicelluloses were present only on the surface of the natural coconut fiber whereas the peak of Fourier Transform Infrared spectra associated with the presence of waxes was observed for natural and chemically treated coconut fibers. The bitumen modified with chemically treated coconut fibers exhibited lower penetration values and higher softening point. From the analyses of penetration value, softening point and penetration index, the bitumen modified with 10% NaOH and 50% CH3COOH treated coconut fibers resulted in enhanced properties for paving binders to be used in warmer region.